Fine Needle Aspiration Cytology of Palpable Cervical Swellings: A One-Year Cross-Sectional Study at a Tertiary Care Hospital - Jinita D. Kathiyara; Puja B. Jarwani; Mansi R. Patel (Annals of Pathology and Laboratory Medicine, 2026)
Background: Fine Needle Aspiration Cytology (FNAC) is a minimally invasive, rapid, and cost-effective diagnostic modality widely employed in the evaluation of cervical swellings. The present study was conducted to analyze the cytomorphological spectrum and classify lesions using standardized reporting systems.Methods: This cross-sectional study was conducted over one year (January–December 2024) in a tertiary care centre. A total of 169 cases of cervical swellings were evaluated by FNAC. Lesions were categorized using the Sydney System (lymph node), Bethesda System (thyroid), and Milan System (salivary gland cytology). Result: Among 169 cases, 108 (63.9%) were lymph node lesions, 30 (17.8%) thyroid, 22 (13%) salivary gland swellings and 9 (5.3%) were from sites like soft tissue and skin. Overall, 142 (84%) were non-neoplastic and 27 (16%) neoplastic. Lymph node lesions were predominantly of Category L2 Benign, with granulomatous lymphadenitis (41.7%) being the most common. Thyroid lesions were mostly benign, Category II (73.6%), chiefly benign follicular nodular disease (43.3%), while sialadenitis belonging to Category II, Non-neoplastic (59.1%) was the most common salivary gland lesion.Conclusion: FNAC is a useful, rapid, and minimally invasive first-line diagnostic modality for the evaluation of cervical swellings. The majority of lesions are benign or inflammatory, and the application of standardized reporting systems such as the Sydney, Bethesda, and Milan frameworks enhances reproducibility, and clinician-pathologist communication.